MANAJEMEN SUMBER DANA DI PONDOK PESANTREN IMAM SYAFI'I BREBES - Akmal, M Izzu Maulal (An Nuqud Journal of Islamic Economics, 2025)
The purpose of this study is to investigate Pondok Pesantren Imam Syafi’i Brebes’ fund management method, which combines contemporary governance concepts with spiritual and Islamic ethical ideals. Using a qualitative methodology, information was gathered via documentation, in-depth interviews, and participatory observation. The results show that the pesantren uses a basic accounting system that is moving toward digitization to manage money from a variety of sources, including grants, contributions, zakat, and profitable enterprises. Over the last two years, business diversification has resulted in a 15% rise in income. Limited management capacity and liquidity problems persist even with a healthy profit margin. In order to improve entrepreneurial education, students actively participate in economic activities. This study recommends strengthening human resource competencies, implementing digital-based evaluation systems, and building strategic collaborations to develop a professional, accountable, and financially independent pesantren